(untitled) (INMR - Innovation & Management Review, 2023)
Purpose – Drawing on the resource-based view (RBV) and knowledge-based view (KBV) theories, this studycontributes to deepen the knowledge that corporate social responsibility (CSR) exerts on firms’ innovation,considering the role played by cooperation. The research also seeks to ascertain the factors that influence thedevelopment of business cooperation. Design/methodology/approach – The database used is the Community Innovation Survey (CIS, 2014)applied in the European Union (EU) during the time period 2012–2014. A sample of 7083 Portuguese firms wereanalyzed through the partial least squares structural equation modeling (PLS-SEM). Findings – The results suggest that CSR positively relates with firms’ innovation, and business cooperationpartially mediates this relationship. The outcomes also reveal that investing in certain types of innovationactivities increases the firms’ willingness to cooperate. Originality/value – The findings contribute to encourage an open innovation strategy as an easy andeffective way to cope with rapid trends and changes, since it demonstrates the complementary betweeninnovation and cooperation, as sources of value creation. From a triple bottom line (TBL) perspective, it alsohighlights that CSR must include social, economic and environmental initiatives, and should be a part of thefirms’ innovation strategy. As a result, managers who intend to contribute for society in the long term shouldplan, monitor and manage all CSR dimensions.